First record and ecological aspects of Hoplerythrinus unitaeniatus (Agassiz, 1829) (Characiformes, Erythrinidae) as introduced species in Rio dos Sinos basin, RS, Brazil - Leal, Mateus Evangelista; Klein, Greice Francisco; Schulz, Uwe Horst; Albornoz, Pablo Lehmann (Biota Neotropica, 2010)
Hoplerythrinus unitaeniatus is popularly known as jeju or aimara. Widely distributed, occurs in many Central and South America basins, with the São Francisco River as type locality. In Brazil, the southernmost record of the species is the Uruguay River, Rio Grande do Sul State. This study reports the first record of H. unitaeniatus in the Patos Lagoon system, Guaiba hydrographic region, state of Rio Grande do Sul, Brazil. The capture occurred in a floodplain adjacent of the Sinos River near São Leopoldo city (29° 44' 14.04" S and 51° 05' 11.08" W). Two specimens were collected with drag net in May 2008. One specimen was anesthetized with 2-phenoxy-ethanol solution, fixed in formalin 10%, identified and included in the Museu de Ciências e Tecnologia da Pontífícia Universidade Católica do Rio Grande do Sul fish collection. The second specimen was kept alive in aquarium. After ten months it died of Lernaea cyprinacea (Crustacea, Copepoda) infestation. The presence of Lernaea and ease of captive breading of this species support the hypothesis that the collected fish escaped from regional fish farms. The accidental capture does not necessarily reflect a self-sustaining population, but shows the absence of supervision on breeding and marketing of non-native species, which may lead to a homogenized aquatic community.